2016
DOI: 10.1051/0004-6361/201527593
|View full text |Cite
|
Sign up to set email alerts
|

On the interpretation and applicability ofκ-distributions

Abstract: Context. The generally accepted representation of κ-distributions in space plasma physics allows for two different alternatives, namely assuming either the temperature or the thermal velocity to be κ-independent. Aims. The present paper aims to clarify the issue concerning which of the two possible choices and the related physical interpretation is correct. Methods. A quantitative comparison of the consequences of the use of both distributions for specific physical systems leads to their correct interpretation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 109 publications
(111 citation statements)
references
References 19 publications
3
108
0
Order By: Relevance
“…first and second kinds, and forms where either the "temperature" or "thermal velocity" is kappa dependent e.g. Lazar et al (2016), Livadiotis (2015Livadiotis ( , 2014, Livadiotis & McComas (2009), Hellberg et al (2009), Leubner (2004. The physical interpretation of the value of κ obtained from the line fitting, in terms of the ion velocity distribution, therefore depends on the form of the ion kappa distribution used.…”
Section: Non-thermal Ion Motionmentioning
confidence: 99%
“…first and second kinds, and forms where either the "temperature" or "thermal velocity" is kappa dependent e.g. Lazar et al (2016), Livadiotis (2015Livadiotis ( , 2014, Livadiotis & McComas (2009), Hellberg et al (2009), Leubner (2004. The physical interpretation of the value of κ obtained from the line fitting, in terms of the ion velocity distribution, therefore depends on the form of the ion kappa distribution used.…”
Section: Non-thermal Ion Motionmentioning
confidence: 99%
“…We have invetigated the effects of suprathermal populations on the plasma waves and instabilities using two alternative approaches, which assume the effective temperature to be either constant (Lazar et al 2011;Mace et al 2011;Lazar 2012), or increasing with the increase of suprathermal populations, i.e., with decreasing the power-index κ (Luebner and Schupfer 2000; Lazar et al 2015Lazar et al , 2016. Being more convenient computationally the approach with a κ-independent temperature has been widely invoked in similar theoretical predictions of plasma instabilities.…”
Section: Governing Dispersion Relationmentioning
confidence: 99%
“…Being more convenient computationally the approach with a κ-independent temperature has been widely invoked in similar theoretical predictions of plasma instabilities. However, have recently shown and Lazar et al (2016) have extended the comparative analysis to add supplementary arguments that a Kappa model with the effective temperature increasing with growing suprathermal population, i.e., with decreasing value of the power index κ, reproduces much better the Maxwellian core in the limit κ → ∞, and thus enables a more realistic characterization of the suprathermal populations and their destabilizing effects. For a collisionless and homogenous electron-proton plasma described by the distributions (1)-(6), the dispersion relations for the electromagnetic modes propagating parallel to the stationary magnetic field read…”
Section: Governing Dispersion Relationmentioning
confidence: 99%
“…The effects of a varying κ (including the Maxwellian limit κ → ∞) are also easier to parametrize if temperature is taken constant. However, for studies intended to outline the effects of suprathermal populations, Lazar et al (2015aLazar et al ( , 2016a have shown that only the approach assuming a κ-dependent temperature may provide a fairly rigorous comparison of the global Kappa describing the observed distribution, with the cooler Maxwellian κ → ∞ limit reproducing the core of the distribution. Moreover, only in this case the instabilities driven by the kinetic anisotropies of plasma particles are systematically stimulated by the suprathermals (i.e., lowering the values of κ), confirming the expectation that these populations should contribute with an additional free energy (Lazar et al 2015a(Lazar et al , 2016b.…”
Section: Introductionmentioning
confidence: 99%
“…However, a global Kappa does not always provide a good fit to the observed distributions, as we will arXiv:1703.01459v1 [physics.plasm-ph] 4 Mar 2017 see here below, e.g., the analysis in section 2 (also Figs. 1 and 2), which suggests that a global Kappa is just a simplified (or idealized) approach that artificially constrains the core and suprathermal populations to be described by the same parameters, e.g., density, temperature, anisotropy (not fully justified yet, although some studies in this direction have been done by Leubner (2004); Lazar et al (2015aLazar et al ( , 2016a). It may be, therefore, that fitting measurements of the observed distributions with global Kappa models can not provide relevant evidences to support any of the two alternatives of a temperature either dependent or independent of the power-index κ.…”
Section: Introductionmentioning
confidence: 99%